2017
DOI: 10.1021/acs.molpharmaceut.7b00555
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Engineered Microbicide Drug Delivery System Targeting HIV-1 gp120: Physicochemical and Biological Properties

Abstract: The purpose of this study was to engineer a model anti-HIV microbicide (tenofovir) drug delivery system targeting HIV-1 envelope glycoprotein gp120 (HIV-1 g120) for the prevention of HIV sexual transmission. HIV-1 g120 and mannose responsive particles (MRP) were prepared through the layer-by-layer coating of calcium carbonate (CaCO) with concanavalin A (Con A) and glycogen. MRP average particle size ranged from 881.7 ± 15.45 nm to 1130 ± 15.72 nm, depending on the number of Con A layers. Tenofovir encapsulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 108 publications
3
43
0
Order By: Relevance
“…Mannosylated compounds, macromolecules, and nanoparticles often undergo specific interaction with mannose receptors (CD206) on cells, which involves receptor-mediated endocytosis and internalization into cytoplasmic compartments. Such biological processes have been reported in the case of various nanoparticles targeted delivery to macrophages [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] . To confirm such specific interactions between MDNPs and U937 cells, we performed a series of uptake assays by varying mannose density on F127-TA nanoparticles and their time-dependent interaction with cells ( Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Mannosylated compounds, macromolecules, and nanoparticles often undergo specific interaction with mannose receptors (CD206) on cells, which involves receptor-mediated endocytosis and internalization into cytoplasmic compartments. Such biological processes have been reported in the case of various nanoparticles targeted delivery to macrophages [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] . To confirm such specific interactions between MDNPs and U937 cells, we performed a series of uptake assays by varying mannose density on F127-TA nanoparticles and their time-dependent interaction with cells ( Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Nanoparticles provide distinct advantages for therapeutic application over traditional delivery methods by improving the targeted efficacy, pharmacokinetics, and bioavailability of the drugs being delivered. Functionalization of an active targeting motif creates opportunity and allows superior targeting of monocytes and macrophages with a high specificity and affinity [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] . Major criteria for construction of such active targeted nanosystems are high ligand density and a favorable orientation for the ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that after 30 minutes of exposure, the concentration released (10 μg/mL) is equivalent to the published IC 90 for the drug. Recently, a research article published by Coulibaly et al 55 utilized HIV-1 gp120 fragment's ability to interact with the drug carrier to trigger drug release. In this study, tenofovir was encapsulated in a mannose responsive particle using calcium carbonate, concanavalin A, and glycogen.…”
Section: State Of the Artmentioning
confidence: 99%
“…27,28 The assembly of the LbL film is based on intermolecular interactions between the materials, so a great interest is dedicated to find suitable materials for alternating with the biomolecule which can retain its specific biological function. [27][28][29][30][31][32] An alternative approach to increase sensitivity is the use of electrical impedance measurements, which are normally employed to exploit changes in dielectric properties, charge distribution and/or thickness of the dielectric layer when an antibody-antigen complex is formed on the electrode surface. [33][34][35] In this paper, we report on electrical impedance measurements for detecting the anti-HCV antibody, again exploiting the biorecognition between the antibody and the antigenic peptide NS5A-1 immobilized in LbL films with SF.…”
Section: Introductionmentioning
confidence: 99%